Stability of space use in svalbard coastal female polar bears: Intra-individual variability and influence of kinship - Brun, Clément; Blanchet, Marie-Anne; Ims, Rolf A.; Aars, Jon (Polar Research, 2021)
Philopatry influences animal distribution and can lead to a kinship-based spatial structure, where proximity and relatedness are tightly linked. In the Barents Sea region, polar bears (Ursus maritimus) of the coastal ecotype remain year-round within the Svalbard archipelago. This coastal strategy is thought to be stable across years; however, little is known about the intra-individual variability in site fidelity or the influence of kinship on space use. Using high-resolution GPS telemetry, we looked at multi-year philopatry among 17 coastal female polar bears over eight years (2011–19) and investigated whether it is linked to the females’ degree of kinship. Individuals showed a stable space use in both consecutive and non-consecutive years. Yearly individual home ranges (HRs) overlapped, on average, by 44% (range: 9–96%), and their centroids were, on average, 15 km (range: 2–63 km) apart. The space use of related females revealed a year-round strong female kin structure. Annual HRs of related females overlapped, on average, by 24% (range: 0–66%), and their centroids were, on average, 18 km (range: 2–52 km) apart. In contrast, non-related females had much larger distances between centroids (average: 160 km, range: 59–283 km). Additionally, females showed a great site fidelity in all seasons: individual seasonal HR centroids were, on average, less than 30 km (range: 1.8–172 km) apart. Bears in this region seem to exhibit a stronger site fidelity than those reported from other parts of the species range. These findings also highlight the importance of maternal learning in space use.